If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) + 3(x + -2) = 0 Reorder the terms: 3(-4 + x) + 3(x + -2) = 0 (-4 * 3 + x * 3) + 3(x + -2) = 0 (-12 + 3x) + 3(x + -2) = 0 Reorder the terms: -12 + 3x + 3(-2 + x) = 0 -12 + 3x + (-2 * 3 + x * 3) = 0 -12 + 3x + (-6 + 3x) = 0 Reorder the terms: -12 + -6 + 3x + 3x = 0 Combine like terms: -12 + -6 = -18 -18 + 3x + 3x = 0 Combine like terms: 3x + 3x = 6x -18 + 6x = 0 Solving -18 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 6x = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 6x = 0 + 18 6x = 0 + 18 Combine like terms: 0 + 18 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| -9y-3=3 | | 56=8xp | | 9x+4y=172 | | 7k+3-6k=-35 | | X+2*2=3x-8 | | -5x-4y=1 | | b+20+7b=50 | | -.5+a=.625 | | 9(x-9.9)=6.3 | | X+2+x+2=3x-8 | | 2(w-3)=1-(v+4) | | 6(3)-3y=18 | | 10(v-5)+4=11(4+5v) | | e^2x-3=10 | | 6(1)-3y=18 | | X-4+3-2x=4x+5-2x | | 4k^2+11k-15=0 | | an=-4n+-7 | | 9d+15=-15 | | 49-14=7-x | | x(2x-1)=2x(2x)+5x-12 | | 2.8x-43=1.3x+2 | | 5x-6=5x-1 | | X+19+x+19=x+29 | | -.15=.40+0.125p | | -9-4+2M=-9-7M+5 | | 24x^2+14x+108=0 | | 3*x^2=8-2x | | h(x)=x^4-4x+2 | | 4(3n-2)=(7n+4)+6 | | 45+3x+r=180 | | -.014x^2+.68x=0 |